On Some Partitions Related to Q(2) - Patkowski, Alexander E. (The Electronic Journal of Combinatorics, 2009)
We offer some new identities for a bipartition function, which has a relation to a Hecke-type identity of Andrews. Further, we show this partition function is lacunary, and relate it to a real quadratic field.